Influence of using emulsified palm biodiesel fuel on the performance and pollutants emitted from diesel engine - Yusop, Ahmad Fitri
As the population growth rapidly, the global energy consumption also increases especially in personal transportation, vehicles. To solve the problem of energy sources, biodiesel is chosen as it is a renewable, sustainable and suitable to use on current diesel engine without modified the engine. Previous researchers also found that biodiesel fuels are cleaner and even more efficient than diesel fuel. This thesis is focused on investigate the characteristics, engine performance and emission of emulsified biodiesel with alcohol. 8 sample fuels which are B5Bu5, B5Bu10, B5Bu15, B5Bu20, B10Bu5, B10Bu10, B10Bu15 and B10Bu20 are prepared to investigate the fuel properties. Then, 3 suitable fuels which are B5Bu5, B5Bu10 and B10Bu5 are continued with engine performance and emission testing and therefore compared with diesel fuel. The parameters that measured for engine performance and exhaust gas emission testing are torque, brake power (BP), brake specific fuel consumption (BSFC), exhaust gas temperature (EGT), nitrogen oxide (NOx), carbon monoxide (CO) and carbon dioxide (CO2). The operating condition for both testing are same which is constant 50% load at various engine speeds (1000rpm, 1500rpm and 2000rpm). In term of characteristic, the density of 8 samples fuels has not significant different with D100 (100% diesel) due to the additive has similar density as D100. However, the calorific value of D100 is 4.3% to 8.7% higher than 8 sample fuels. In term of engine performance, BP of sample fuels is reduced 4 to14% as compared to D100. B5Bu5 shows a lowest average of BSFCs over entire engine speeds. In term of emission, the average emission of NOx is slightly higher than D100 with 7%. However, the CO emission of B5Bu5 is significantly reduced by 30.2% as compared to D100, whereas CO2 resulted opposite way which B5Bu5 increased by 28.8% as compared to D100. This is because of the oxygen-rich regions brings by oxygenated fuels and micro-explosions that promote the complete combustion. Therefore, B5Bu5 is the greatest fuel among the 8 sample fuels in overall characteristics, engine performance and exhaust gas emission.